Protein and gene expression characteristics of a rice phosphoenolpyruvate carboxylase Osppc3; its unique role for seed cell maturation. (July 2015) - Yamamoto, Naoki; Sasou, Ai; Saito, Yuhi; Sugimoto, Toshio; Masumura, Takehiro
Abstract: Phospho enol pyruvate carboxylase (PEPCase) has been considered a probable key enzyme for seed development. We previously isolated cDNA of a PEPCase isogene Osppc3 from developing rice seeds. However, its physiological role has been unclear. Here, we report an expression analysis of Osppc3 in developing seeds at the protein and mRNA levels. Osppc3 protein was preferentially expressed in developing seeds at an early stage, from 3 to 14 DAF, and was localized in the embryo and in the aleurone layer, the cells of which accumulate storage lipids. Co-expression analysis of Osppc3 revealed a gene expression pattern similar to those of fatty acid biosynthetic pathway genes as well as ribosomal protein genes and DNA replication genes, implying that Osppc3 cooperates with those gene products in seed development. We validated similarity of gene expression patterns of these genes by semi-quantitative RT-PCR in developing seeds. The gene expression pattern of Osppc3 was related to triacylglycerol accumulation in embryo and aleurone layer cells. Microscopic observations of embryo and aleurone layer tissues also revealed differences in the timepoint at which triacylglycerol drastically accumulates during cell maturation. These results indicate that Osppc3 should play roles in both the arrangements of cell components and storage lipid accumulation in rice seeds. Highlights: The dynamics of a PEPCase Osppc3 protein in developing rice seeds were disclosed. Osppc3 is localized in embryo and aleurone cells during lipid accumulation stage. Co-expression of Osppc3 and the fatty acid biosynthetic pathway genes was found. Different triacylglycerol accumulation patterns in embryo and endosperm were shown.